THE EFFECT OF DIABETIC FOOT EXERCISES ON REDUCING BLOOD SUGAR LEVELS IN DIABETES MELLITUS PATIENTS IN ACEH: A CASE STUDY - Fakruddin Fakruddin; Aulia akmal; Rudi Alfiandi (Getsempena Health Science Journal, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by impaired insulin production or function, resulting in persistent hyperglycemia. This condition can lead to serious complications and negatively impact patients’ quality of life. Among various non-pharmacological approaches, diabetic foot exercises have emerged as a simple, effective, and accessible method for managing blood glucose levels. This study aims to evaluate the effectiveness of diabetic foot exercises in reducing blood glucose levels and assess their potential for community-level implementation. A descriptive case study design was used, involving two subjects with elevated blood glucose and cholesterol levels. The intervention was carried out over seven consecutive days in a rural village in Aceh. Data were collected through structured interviews and direct observation before and after the intervention, using assessment forms, observation sheets, and standard operating procedures for glucose monitoring. The results showed a significant decrease in blood glucose levels in Subject I, from 342 mg/dL to 280 mg/dL, and a marked reduction in cholesterol levels in Subject II, from 214 mg/dL to 74 mg/dL. The exercises are believed to stimulate lower limb muscle activity, increasing energy demand and promoting glucose uptake through metabolic pathways such as glycogenesis. Due to their simplicity, low cost, and ease of implementation, diabetic foot exercises present a promising alternative therapy, especially in resource-limited settings. Patient adherence and health education are critical to the success of this intervention. These findings support the inclusion of diabetic foot exercises in community-based diabetes management programs and contribute valuable insights for future public health strategies.